2015
DOI: 10.1002/2015wr017144
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed convective rainfall by agricultural expansion in southeastern Burkina Faso

Abstract: With the “green economy” being promoted as a path to sustainable development and food security within the African continent, the influx of agricultural land is proliferating at a rapid pace often replacing natural savannah forests. Where agriculture is primarily rainfed, the possible adverse impacts of agricultural land influx on rainfall occurrences in water‐limited areas such as West Africa warrant attention. Using field observations complemented by model calculations in southeastern Burkina Faso, the main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…A time-based snail sampling technique was used analogously to the ones previously used in similar malacological studies ( 6,7,30). Along with snail sampling, a network of wireless micrometeorological stations was installed in each village, allowing for the continuous monitoring of microclimatic and hydrological parameters, including air temperature, water level, conductivity and temperature, and precipitation (36). Details are given in the SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…A time-based snail sampling technique was used analogously to the ones previously used in similar malacological studies ( 6,7,30). Along with snail sampling, a network of wireless micrometeorological stations was installed in each village, allowing for the continuous monitoring of microclimatic and hydrological parameters, including air temperature, water level, conductivity and temperature, and precipitation (36). Details are given in the SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…While this does not measure the occurrence or depth of actual convective storms, it provides a simple indicator of whether the atmosphere is predisposed to convective rainfall at a given time and is considered a necessary condition for the occurrence of convective rainfall [Juang et al, 2007]. Using this method with simple boundary layer growth models has proven a useful tool for gaining insight into how competing mechanisms of boundary layer growth and entrainment can modify convective rainfall [Daly et al, 2004;Mande et al, 2015;Manoli et al, 2016]. For example, using similar simple boundary layer growth model, Mande et al [2015] found that all instances of measured convective rainfall at their semiarid study site were preceded by an LCL crossing.…”
Section: Assessing Boundary Layer Differencesmentioning
confidence: 99%
“…Using this method with simple boundary layer growth models has proven a useful tool for gaining insight into how competing mechanisms of boundary layer growth and entrainment can modify convective rainfall [Daly et al, 2004;Mande et al, 2015;Manoli et al, 2016]. For example, using similar simple boundary layer growth model, Mande et al [2015] found that all instances of measured convective rainfall at their semiarid study site were preceded by an LCL crossing. There is a strong empirical relationship between daily crossing statistics and bias-corrected rainfall rate and cumulative rainfall across all sites and both months (supporting information section S2 and Figures S1 and S2) [Reichle et al, 2016], confirming the relevance of LCL crossings as a proxy of convective precipitation.…”
Section: Assessing Boundary Layer Differencesmentioning
confidence: 99%
“…The malacological data was collected in two field sites located in Burkina Faso (West Africa) along the South-North climatic gradient between the Sudanian and Sahelian climatic regions (Fig 1a, detailed description given in [24]). Annual rainfall in these climatic zones ranges from 350mm to 1100mm per year, and presents a marked seasonal variation with most precipitation occurring during the rainy season between July and September and only very limited precipitation events the rest of the year (Fig 1) [45]. Both intestinal and uro-genital schistosomiasis are present in the country [46].…”
Section: Field Sitesmentioning
confidence: 99%